2022
DOI: 10.3389/fnins.2022.936760
|View full text |Cite
|
Sign up to set email alerts
|

Review on the roles of specific cell-derived exosomes in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is the sixth leading cause of death worldwide and cannot be effectively cured or prevented; thus, early diagnosis, and intervention are important. The importance of exosomes, membrane-bound extracellular vesicles produced in the endosome of eukaryotic cells, in the development, diagnosis, and treatment of AD has been recognized; however, their specific functions remain controversial and even unclear. With the development of exosome extraction, isolation, and characterization, many stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 127 publications
0
8
0
Order By: Relevance
“…The latter results in the production of Aβ that can be either degraded in the lysosomes or dumped into extracellular space. FRET and other experimental evidence have indicated that BACE interacts with APP in the endosomes and preventing of surface endocytosis blocks almost 80% of Aβ release ( Koo and Squazzo, 1994 ; Kinoshita et al, 2003 ; Fukumori et al, 2006 ; Zou et al, 2022 ). These experimental evidence indicates the role of exosomes in releasing Aβ peptides into the extracellular spaces and their uptake by other neuronal cells.…”
Section: Role Of Extracellular Vesicles In Dissemination Of Pathogeni...mentioning
confidence: 99%
“…The latter results in the production of Aβ that can be either degraded in the lysosomes or dumped into extracellular space. FRET and other experimental evidence have indicated that BACE interacts with APP in the endosomes and preventing of surface endocytosis blocks almost 80% of Aβ release ( Koo and Squazzo, 1994 ; Kinoshita et al, 2003 ; Fukumori et al, 2006 ; Zou et al, 2022 ). These experimental evidence indicates the role of exosomes in releasing Aβ peptides into the extracellular spaces and their uptake by other neuronal cells.…”
Section: Role Of Extracellular Vesicles In Dissemination Of Pathogeni...mentioning
confidence: 99%
“…Likewise, miR‐342‐3p was downregulated in plasma exosomes, whereas miR‐212 and miR‐132 were downregulated in neural exosomes 181 . miRNAs, such as miR‐9‐5p, miR‐598, miR‐125b, miR‐29, miR‐342‐3p, and miR‐193b, are highly stable and resistant to degradation in exosomes before the onset of AD, suggesting their promising roles as biomarkers for the early clinical diagnosis and monitoring of AD 182,183 . miR‐29c‐3p, miR‐384, and nerve cell adhesion molecule in double‐labeled exosomes have the potential for early diagnosis of AD 184,185 .…”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 99%
“… 181 miRNAs, such as miR‐9‐5p, miR‐598, miR‐125b, miR‐29, miR‐342‐3p, and miR‐193b, are highly stable and resistant to degradation in exosomes before the onset of AD, suggesting their promising roles as biomarkers for the early clinical diagnosis and monitoring of AD. 182 , 183 miR‐29c‐3p, miR‐384, and nerve cell adhesion molecule in double‐labeled exosomes have the potential for early diagnosis of AD. 184 , 185 Serum exosomal miR‐185‐5p was significantly downregulated in AD patients and mice as compared with the control group.…”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Purifying specific EVs derived from the brain may circumvent these limitations and enable the investigation of their cargos as biomarkers of brain disorders. Recent studies have reported the existence of neuron-derived EVs (NDEs), astrocyte-derived EVs (ADEs), and oligodendrocyte-derived EVs (ODEs) in the brain ( Zou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%